Finite element modelling and analysis of composite B-Pillar - M. I., Ibrahim; Mohd Ruzaimi, Mat Rejab; H., Hazuan; M. F., Rani (AIP Publishing, 2019)
B-Pillars are specifically designed to absorb substantial energy with a minimum amount of deformation to limit its intrusion in the passenger compartment during an event of side impact. In this paper, the B-pillar has been developed using composite materials, with the main objective is to improve crashworthiness performance at a lesser weight, as a replacement for steel. The three-point bending test simulations of the composite B-pillar model were modelled, which applied various parameters of materials, number of ply and additional reinforcement. The composite B-pillar design parameter that scored the highest performance to weight ratio in the numerical simulation was then fabricated using vacuum bagging method. Subsequently, the B-pillar was tested under three-point bending experimental work. The force and central displacement results were compared to simulation data and a good agreement was obtained, where B-pillar made of carbon fibre reinforced polymer (CFRP) performed better than glass fibre reinforced polymer (GFRP). The simulation and experimental results indicated errors ranging between 6 and 15%. With the additional reinforcement at the critical area, the energy absorption of CFRP B-pillar was considerably improved by 18%. The weight of the fabricated composite B-pillar was 58% lighter compared to the original steel B-pillar. These results confirmed that the novel composite material holds a high strength, and has lightweight potential to substitute steel as car B-pillar material.